Survivors of standard risk acute lymphoblastic leukemia do not have increased risk for overweight and obesity compared to non‐cancer peers: A report from the Children's Oncology Group. Issue 6 (7th February 2015) - Lindemulder, Susan J.; Stork, Linda C.; Bostrom, Bruce; Lu, Xiaomin; Devidas, Meenakshi; Hunger, Stephen; Neglia, Joseph P.; Kadan‐Lottick, Nina S.
<x xml:space="preserve">Abstract</x> Background We sought to determine whether survivors of standard risk ALL (SR‐ALL) treated without cranial radiation have increased risk for obesity by assessing changes in body mass index (BMI) during and after treatment; identifying contributing patient and treatment factors; comparing rates of overweight/obese to national health data. Procedure Eligibility for this retrospective cohort study included: (i) previous enrollment on legacy therapy trials CCG1922 or CCG1952; (ii) continuous first remission; and (iii) age at follow‐up evaluation of 6–16.99 years. Height and weight from diagnosis, consolidation, start of maintenance, last cycle of maintenance, and off‐therapy were analyzed. Results The 269 subjects were a median age of 3.5 years at diagnosis and 13.3 years at follow‐up. BMI% significantly increased from induction to consolidation (+17.6 ± 1.6%), start of maintenance to end‐of‐treatment (+3.3 ± 1.6%) and decreased from end‐of‐treatment to follow‐up (−3.5 ± 1.6%, ). Higher BMI% at follow‐up was associated with higher BMI% at diagnosis (P < 0.0001), but not age at diagnosis, gender, or race. Patients previously randomized to dexamethasone had a stronger association between BMI% at diagnosis and BMI% at follow‐up than those who received prednisone (P = 0.0005). At follow‐up, 39% of survivors were overweight or obese; the relative risk of overweight/obese was 1.028 (P = 0.738) compared to the general population. Conclusions Our study of patients with SR‐ALL found a significant increase in BMI% largely during the first month of therapy that is greater with dexamethasone than prednisone. However, after therapy, there was no increased risk of overweight/obese BMI compared to non‐cancer peers. Pediatr Blood Cancer 2015;62:1035–1041. © 2015 Wiley Periodicals, Inc.